Early Commissural Diencephalic Neurons Control Habenular Axon Extension and Targeting - Beretta, Carlo Antonio; Dross, Nicolas; Guglielmi, Luca; Bankhead, Peter; Gutiérrez Triana, José Arturo; Paolini, Alessio; Poggi, Lucia; Ryu, Soojin; Engel, Ulrike; Carl, Matthias (Current biology, 2017)
Summary Most neuronal populations form on both the left and right sides of the brain. Their efferent axons appear to grow synchronously along similar pathways on each side, although the neurons or their environment often differ between the two hemispheres [1-4]. How this coordination is controlled has received little attention. Frequently, neurons establish interhemispheric connections, which can function to integrate information between brain hemispheres (e.g., [5]). Such commissures form very early, suggesting their potential developmental role in coordinating ipsilateral axon navigation during embryonic development [4]. To address the temporal-spatial control of bilateral axon growth, we applied long-term time-lapse imaging to visualize the formation of the conserved left-right asymmetric habenular neural circuit in the developing zebrafish embryo [6]. Although habenular neurons are born at different times across brain hemispheres [7], we found that elongation of habenular axons occurs synchronously. The initiation of axon extension is not controlled within the habenular network itself but through an early developing proximal diencephalic network. The commissural neurons of this network influence habenular axons both ipsilaterally and contralaterally. Their unilateral absence impairs commissure formation and coordinated habenular axon elongation and causes their subsequent arrest on both sides of the brain. Thus, habenular neural circuit formation depends on a second intersecting commissural network, which facilitates the exchange of information between hemispheres required for ipsilaterally projecting habenular axons. This mechanism of network formation may well apply to other circuits, and has only remained undiscovered due to technical limitations.